Regenerative pharmacology - Christ, George J.; Andersson, Karl-Erik (Cambridge University Press, 2013)
"Regenerative medicine is broadly defined as the repair or replacement of damaged cells, tissues, and organs. It is a multidisciplinary effort in which technologies derive from the fields of cell, developmental, and molecular biology; chemical and material sciences (i.e., nanotechnology); engineering; surgery; transplantation; immunology; molecular genetics; physiology; and pharmacology. As regenerative medicine technologies continue to evolve and expand across the boundaries of numerous scientific disciplines, they remain at the forefront of the translational research frontier with the potential to radically alter the treatment of a wide variety of disease and dysfunction. The goal of this book is to draw attention to the critical role that the pharmacological sciences will undeniably play in the advancement of these treatments. This book is invaluable for advanced students, postdoctoral fellows, researchers new to the field of regenerative medicine/tissue engineering, and experienced investigators looking for new research avenues. This is the first state-of-the-art book in this rapidly evolving field of research"--Provided by publisher.